Relationship Between Dentofacial Features and Bullying in Schoolchildren - Maia, Paulo Roberto Martins; Fialho, Tiago; Freitas, Karina Maria Salvatore; Cotrin, Paula; Valarelli, Fabricio Pinelli; Tavares, Rudys Rodolfo de Jesus; Gurgel, Julio de Araujo [UNESP]; Pinzan-Vercelino, Celia Regina Maio (Amer Acad Pediatric Dentistry, 2024)
Purpose: The purpose of this cross-sectional study was to evaluate the association between clinician -assessed (actual) and self -assessed (perceived) dentofacial features and their association with bullying in schoolchildren. Methods: The sample comprised 519 schoolchildren aged 10 to 12 years old (235 boys and 284 girls) randomly selected from private and public schools. Clinical evaluations were performed to record dentofacial features, and the children were asked a self -reported questionnaire about their personal experience of bullying and perceived dentofacial features. Descriptive statistics (counts and percentages) as well as chi-square to analyze the association between variables were applied. Results: The results showed that 57.2 percent of the children reported being bullied, and the mainly perceived dentofacial features cited were: crooked teeth (46.3 percent), shape or color of teeth (45.5 percent), upper front teeth sticking out (43.8 percent), and having a gap between the teeth or having missing teeth (35.5 percent). Statistically significant associations between actual and perceived dentofacial features and involvement in bullying were observed for anterior crowding (P=0.01), anterior crossbite (P<0.001), lip competence (P=0.008), and anterior dental trauma (P=0.04). Conclusion: Some actual and perceived dentofacial traits are associated with bullying, so these features and the schoolchildren's compliances should be considered to determine the treatment need. (Pediatr Dent 2024;46(2):99-107) Received June 30, 2023 | Last Revision November 8, 2023 | Accepted November 13, 2023
Keywords: BULLYING; MALOCCLUSION; DIAGNOSTIC SELF EVALUATION